2012
DOI: 10.3724/sp.j.1005.2012.01522
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the molecular genetics of brachydactyly

Abstract: Brachydactyly (BD) is a general term that refers to shortening of the hands/feet due to small or missing metacarpals/metatarsalsand/or phalanges, and forms part of the group of limb malformations characterized by bone dysostosis. It may occur either as an isolated trait or as part of a syndrome. BD may also be accompanied by other hand mal-formations, such as syndactyly, polydactyly, reduction defects, and symphalangism. In isolated brachydactyly, the inheritance is mostly autosomal dominant with variable expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Brachydactyly is a general term describing extremity malformations characterised by bone dysostosis, with the meaning of disproportional shortness in the fingers and toes which develops due to smallness or absence of metacarpals, metatarsals or phalanxes 1 . Previous studies have shown that bone morphogenic (BMP) pathways play a key role in the normal development of digits and their joints and that these pathways are associated directly or indirectly with the genes of brachydactyly disease 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Brachydactyly is a general term describing extremity malformations characterised by bone dysostosis, with the meaning of disproportional shortness in the fingers and toes which develops due to smallness or absence of metacarpals, metatarsals or phalanxes 1 . Previous studies have shown that bone morphogenic (BMP) pathways play a key role in the normal development of digits and their joints and that these pathways are associated directly or indirectly with the genes of brachydactyly disease 3 .…”
Section: Discussionmentioning
confidence: 99%